# Factorize:(l + m)2 – 4lm

Given,

(l + m)2 – 4lm

By using the formula (a + b)2 = a2 + b2 + 2ab

We get,

(l + m)2 – 4lm = (l2 + m2 + 2lm) – 4lm

= l2 + m2 + 2lm – 4lm

= l2 + m2 – 2lm

= (l)2 + (m)2 - 2×l×m

= (l – m)2

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Algebraic Identities - Mark your Weak Areas41 mins
Quiz | Important Questions on Factorisation35 mins
Quiz | Questions on Factorization41 mins
Champ Quiz | Division of Polynomials33 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

ab - a - b + 1 = ?

RS Aggarwal - Mathematics

Factorize:

x2 + x – 132

RS Aggarwal - Mathematics

2x2 + 5x + 3=?

RS Aggarwal - Mathematics

Factorize:

3m2 + 24m + 36

RS Aggarwal - Mathematics